2014
DOI: 10.1111/ejn.12414
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of pain in early life: injury‐induced plasticity in developing pain pathways

Abstract: Pain in infancy influences pain reactivity in later life, but how and why this occurs is poorly understood. Here we review the evidence for developmental plasticity of nociceptive pathways in animal models and discuss the peripheral and central mechanisms that underlie this plasticity. Adults who have experienced neonatal injury display increased pain and injury-induced hyperalgesia in the affected region but mild injury can also induce widespread baseline hyposensitivity across the rest of the body surface, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
181
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(194 citation statements)
references
References 112 publications
(174 reference statements)
6
181
1
6
Order By: Relevance
“…acute or repeated injury, inflammatory agents, surgical incision; see reviews [38,39]), findings support clinical data showing long-term changes in response to pain and stress, affective behavior and cognition. For example, adult rats exposed to surgery or inflammatory pain in the first postnatal week (developmentally comparable to a 24-36 GW infant [40]) exhibit significant hypo-sensitivity to acute thermal or mechanical noxious stimuli, but hyper-sensitivity to chronic, more intense nociceptive stimulation [41,42].…”
Section: The Long-term Impact Of Early Life Pain In Humanssupporting
confidence: 72%
“…acute or repeated injury, inflammatory agents, surgical incision; see reviews [38,39]), findings support clinical data showing long-term changes in response to pain and stress, affective behavior and cognition. For example, adult rats exposed to surgery or inflammatory pain in the first postnatal week (developmentally comparable to a 24-36 GW infant [40]) exhibit significant hypo-sensitivity to acute thermal or mechanical noxious stimuli, but hyper-sensitivity to chronic, more intense nociceptive stimulation [41,42].…”
Section: The Long-term Impact Of Early Life Pain In Humanssupporting
confidence: 72%
“…It is believed that the mechanism of birth influences pain perception. Previous research has found that new-borns born by assisted vaginal birth have the highest severity of pain, compared to those born by the normal mechanism or Caesarean section [10,11]. The comparison of the severity of pain in children born by normal birth and Caesarean section in this study supports the results of our study, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Animal models of early life pain support clinical findings demonstrating a long-term impact on subsequent responses to pain and stress (Schwaller and Fitzgerald, 2014). Acute or repeated exposure to early life pain induced by foot shock, surgery, or inflammatory agents results in general thermal or mechanical hypoalgesia (i.e.…”
Section: 2 Early-life Pain Impairs Stress and Pain Respondingmentioning
confidence: 79%